Effect of engineered nanoparticles on growth of Lemna sp - Hương, Trần Thị Thu; Kim, Đặng Đình; Thư, Hà Phương; Cường, Hồ Tú; Kiên, Nguyễn Trung; Thúy, Nguyễn Thị; Hà, Trần Thị Kim; Hà, Trần Hồng; Thủy, Dương Thị (Vietnam Journal of Biotechnology, 2016)
Nanotechnology is the technology relating to the synthesis and application of materials with nanometer sizes (nm). At the nanoscale, materials will have special features than traditional materials because their specific size is smaller than 100 nm, larger surface to volume ratio, crystalline structure, high reactivity potential, creating the effect of resonance Plasmon surface... Materials application process also potential risks to health and the environment. To evaluate the safety of nanomaterial in water environment, the experiments on aquatic organisms should be carried out to test the toxicological effects of nanomaterial. Duckweed used as a model organism because of unique difference characteristics from other plants as they could provide a new material source for the production of fuel and biogas, rapidly grow in a short time that requires little soil and nutrition. Duckweed is aquatic plants are widely used in the treatment of water pollution because it has the ability to absorb the nutrients of nitrogen and phosphorus. The aim of this work was to evaluate the influence of silver nanoparticles on growth of Lemna sp. The silver nanoparticles were synthesized by electrochemical and reduction method. Characterizations of these nanoparticles were Transmission electron microscopy (TEM), Scanning Electron Microscope (SEM) and Ultraviolet-Visible (UV - VIS) methods. The weight of Lemna sp. was compared between the first day and the last day of the experiment period (7 th day of cultivation). The results showed that nano materials show growth inhibition against Lemna sp. At concentration of 1 and 5 ppm of silvernano solutions, a maximum anti-Lemna sp. activity was observed